Volatility and financial intermediation - Aizenman, Joshua 1949-; Powell, Andrew (1997)
Following the Tequila period, its after-effects in Latin America and recent events in South East Asia, the effect of volatility on emerging market economies has become an important topic of research with the domestic financial intermediation process being advanced as one of the most important transmission mechanisms. At the same time there has been continued interest in issues related to imperfect information and rationing in credit markets. In this paper, we consider an economy where risk neutral banks provide intermediation services and risk neutral producers demand credit to finance their working capital needs. Our model blends costly state verification with imperfect enforcement power and, in this context of costly financial intermediation, we show that a weak legal system combined with high information verification costs leads to large, first-order effects of volatility on production, employment and welfare. A calibration illustrates that the semi-elasticity of welfare with respect to volatility is less than -1 for reasonable parameter values (i.e., a one percent increase in the coefficient of variation of productivity shocks would reduce welfare by more than one percent). We suggest that legal and information problems in the credit market may then be at the heart of the reason why volatility has profound effects on emerging market economies.
Keywords: Ökonometrisches Modell; Credit -- Econometric models; Intermediation (Finance) -- Econometric models